Does the Use of Ultrasound Affect Contamination of Musculoskeletal Injections Sites?. Issue 1 (January 2015) - Sherman, Thomas; Ferguson, Joseph; Davis, William; Russo, Matthew; Argintar, Evan
Abstract: Background: Therapeutic musculoskeletal injections require a clean or sterile skin preparation to minimize the risk of infections. Ultrasound guidance for this procedure requires the use of transmission gel in proximity to the injection site, and its effect on maintaining sterility is unknown. Questions/purposes: We asked: (1) Does sterile ultrasound transmission gel increase skin contamination during therapeutic orthopaedic injections? (2) Does nonsterile gel application result in increased contamination? (3) Does a manufacturer‐approved ultrasound probe disinfecting agent in the form of 17.2% isopropanol and 0.28% diisobutylphenoxyethoxyethyl dimethyl benzyl ammonium chloride wipes adequately decontaminate the ultrasound transducer? (4) Does 70% isopropyl alcohol effectively decontaminate skin for administration of musculoskeletal injections? Methods: Twenty‐six healthy volunteers in an outpatient orthopaedic clinical setting were recruited. The subjects' skin was prepared to simulate a therapeutic intraarticular shoulder injection under ultrasound guidance. Four skin swabs for culture from each subject were taken: one sample before preparation with isopropyl alcohol, one sample after skin preparation, one after simulated injection procedure with sterile ultrasound transmission gel using the transducer, and one after mock procedure with nonsterile ultrasound transmission gel. In addition, samples were taken from the nonsterile ultrasound transmission gel and the transducer for culture analysis. Aerobic and anaerobic cultures were incubated during a 5‐day period for bacterial species identification. Results: Sterile ultrasound gel use results in an increase in skin contamination (odds ratio [OR], 9; 95% CI, 1.4‐57.1; p = 0.005). Compared with sterile gel use, application of nonsterile gel did not increase contamination proportion (OR, 1.1; 95% CI, 0.8‐1.7; p = 0.56). All cultures from nonsterile gel were negative. None of the samples cultured directly from the ultrasound probe were positive for bacteria (0%). Skin preparation with 70% alcohol decreased the proportion of contamination when compared with unprepared skin (OR, 21.0; 95% CI, 3.1‐142.2; p = 0.001). Conclusions: Use of ultrasound probes and transmission gel results in greater contamination in simulated intraarticular injections of the shoulder. As such, sterile preparation of the entire injection field, including the adjacent skin where the gel and probe are applied, may be prudent. Future studies are needed to determine if such a preparation decreases contamination and thereby infection rates related to musculoskeletal injections. Level of Evidence: Level II, therapeutic study. See the Instructions for Authors for a complete description of levels of evidence.